study of the uses and results of platelet rich plasma in chronic non healing wounds (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction: Platelet-rich Plasma (PRP) is an autologous product, made from anticoagulated blood that has been centrifuged to increase the concentration of platelets compared to whole blood. Chronic cutaneous wounds are frequent problem in developing counties & are often difficult to heal because they lack the growth factors necessary for the healing process & are frequently complicated by super infection. Conventional therapies such as dressings, surgical debridement, and even skin graft cannot provide satisfactory healing since these treatments are not able to provide enough necessary growth factors to modulate the healing process. PRP has become a valuable adjunct in wound healing in plastic surgery. Each growth factor has the capability to induce a unique response in the enhancement of healing thus accelerating and enhancing the natural wound healing of the body. The aim of this study is to assess the effects of platelet-rich plasma (PRP) in chronic non healing wounds.Methods: This prospective study included patients attending outpatient and inpatient facility of Burns & Plastic surgery Department. , 17 patients with Chronic ulcers not healing after 6 weeks treatment with dressing or other adjuvant, etiology chronic venous ulcers, post burn ulcers, post traumatic ulcers, diabetic ulcers, tropical ulcers, etc. were included.Results: With 100% healing of chronic ulcers after PRP infiltration at margins of ulcer, it is found that PRP is a good modality for treatment of chronic ulcer which is reluctant to heal by dressings for long duration.Conclusion: The study was successfully completed during the period of October 2013 to February 2016.Applicability and Efficacy of PRP was found in variety of chronic ulcers due to varicose vein, pressure sore, post burn or trauma. With 100% healing of chronic ulcers after PRP injection, with no complication of PRP, it can be satisfactorily used in patients with chronic wounds.
Keywords: Platelet rich plasma; chronic ulcers; non healing wound